Population Dynamics of the Indonesian Mantis Shrimp, Harpiosquilla raphidea (Fabricius 1798) (Crustacea: Stomatopoda) Collected from a Mud Flat in Kuala Tungkal, Jambi Province, Sumatera Island - Yusli Wardiatno; Ali Mashar (Marine Science Department Diponegoro University, 2011)
This study aim was to reveal the population structure, growth, life span and exploitation rate of mantis shrimp (Harpiosquilla raphidea Fabricius, 1798). This research was conducted in Kuala Tungkal, Tanjung Jabung Barat, Jambi from July 2009 to June 2010 and partially carried out periodically. The results showed the difference in group size distribution between the mantis shrimp caught in the intertidal and those caught in subtidal areas. The length of the mantis shrimps in the intertidal area ranged from 25 to 233 mm with the dominant length was 7996 mm, while in the subtidal area the length ranged from 160-366 with dominant length between 193-258 mm. Growth coefficient (K) was 0.14 for males and 0.11 for females; while L∞ was the same for the two sexes, i.e. 381.68 mm. The life-span of the shrimp was estimated to be 6.7 to 8.5 years. The value of exploitation rate (E) was 0.42 indicating a not optimum exploitation rate of the shrimp. Key words: mantis shrimp, growth, exploitation rate, life-span, Kuala Tungkal Penelitian ini bertujuan untuk mengungkapkan struktur populasi, pertumbuhan, lama mass hidup, dan laju ekspoitasi dari udang mantis (Harpiosquilla raphidea Fabricius, 1798). Penelitian ini dilakukan secara periodik di Kuala Tungkal, Tanjung Jabung Barat, Jambi dari Juli 2009 hingga Juni 2010. Hasil penelitian memperlihatkan adanya dua kelompok ukuran yang berbeda di daerah intertidal dengan di daerah subtidal. Ukuran panjang udang mantis yang hidup di daerah intertidal berkisar 25-233 mm dengan kelompok dominan berukuran 79-96 mm, sedangkan di daerah subtidal ukuran panjang udang mantis adalah 160-366 mm dengan kelompok dominan berukuran 193-258 mm. Koefisien pertumbuhan (K) adalah 0,14 untuk jantan dan 0,11 untuk betina; sementara L∞ kedua jenis kelamin adalah sama yakni 381,68 mm. Lamanya masa hidup jenis udang mantis ini diperkirakan antara 6,7 sampai 8,5 tahun. Nilai laju eksploitasi (E) sebesar 0,42 mengindikasikan laju yang belum optimum. Kata kunci: Udang mantis, pertumbuhan, laju eksploitasi, masa hidup, Kuala Tungkal